The conditions of local change: Kent County Council since reorganization - Holliday, Ian
According to the author, this article considers the conditions of local change through investigation of the experience of Kent County Council since local government reorganization in 1974, seeking both to assess the nature of change in Kent, and to derive from that assessment more general lessons. It argues that in a period of rapid change in local government's operating environment, local change has been locally mediated to a significant extent. It therefore contends that a manipulative account of local change is best able to account for reform at the local level, and maintains that any attempt to explain the differential experience of the Thatcher decade must break the concept of local government down, and
Keywords: Kent County Council; Administrative Reorganization; Local Government - U.K